Portfolio Entrepreneurs’ Behavior and Performance: A Resource Redeployment Perspective - Santamaria, Simone (Management Science, 2022)
Prior research suggests portfolio entrepreneurs—businesspeople who run more than one firm simultaneously—launch more successful ventures than their single-business counterparts. However, their ventures are less likely to survive. In an attempt to reconcile this paradox, this paper presents a framework in which portfolio entrepreneurs’ main advantage is not a superior ability to select the best business opportunities ex ante, but rather the ability to redeploy human and capital resources across businesses ex post, which reduces the sunkenness of their investments in new projects. This redeployment option facilitates their exit from new businesses that fail initial market tests. Thus, portfolio entrepreneurs’ heterogeneous termination decisions explain a greater portion of new firm performance differential than ex ante opportunity selection. We test these ideas using a longitudinal data set of more than 5,700 entrepreneurs and find consistent evidence. Portfolio companies do not show systematically higher performance at the time of entry; a performance difference emerges only over time, as the selection effect and resource redeployment occur. This paper was accepted by Ashish Arora, entrepreneurship and innovation.